2018
DOI: 10.3390/toxins10030124
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl Sulfate Promotes Macrophage IL-1β Production by Activating Aryl Hydrocarbon Receptor/NF-κ/MAPK Cascades, but the NLRP3 inflammasome Was Not Activated

Abstract: In chronic kidney disease (CKD) patients, accumulation of uremic toxins is associated with cardiovascular risk and mortality. One of the hallmarks of kidney disease-related cardiovascular disease is intravascular macrophage inflammation, but the mechanism of the reaction with these toxins is not completely understood. Macrophages differentiated from THP-1 cells were exposed to indoxyl sulfate (IS), a representative uremic toxin, and changes in inflammatory cytokine production and intracellular signaling molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 31 publications
2
38
0
1
Order By: Relevance
“…The pro-oxidant and pro-inflammatory effects of PTUB are related to the intricate signaling cascade of ROS/ MAPK pathways in diverse cell models [14][15][16]. Nonetheless, data about therapeutic targeting PCS induced MAPK activation in HASMC are still lacking.…”
Section: Pcs Triggers Phosphorylation Of the Mapk Family Members (Jnkmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro-oxidant and pro-inflammatory effects of PTUB are related to the intricate signaling cascade of ROS/ MAPK pathways in diverse cell models [14][15][16]. Nonetheless, data about therapeutic targeting PCS induced MAPK activation in HASMC are still lacking.…”
Section: Pcs Triggers Phosphorylation Of the Mapk Family Members (Jnkmentioning
confidence: 99%
“…Apoptotic bodies derived from HASMCs may also act as crystal nucleation for calcium deposition [13]. The underlying mechanism involved in PTUB have been attributed by various signaling pathways including ROS/c-Jun N-terminal kinase (JNK)/P38/mitogen-activated protein kinases (MAPK) [14], aryl hydrocarbon receptor (AhR)/nuclear factor kappa B (NFκB)/ MAPK [15], and ROS-activated NF-κB/extracellular signal-regulated kinases (ERK)/ JNK cascades [16]. In vitro, IS accentuated Pi-induced VSMC calcification and osteogenic transition through increasing Pit-1 expression [17] and oxidative stress [17].…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the UTs that accumulate in brain tissue during CKD might impact the polarization of infiltrated monocytes/macrophages. In line with this observation, IS has been reported to directly induce monocyte-mediated inflammation and ROS production in THP-1 monocytes via the NADPH oxidase and MAPK pathways [ 123 ] and display direct pro-inflammatory effects in vitro via activation of the NF-kB and MAPK pathways in macrophages differentiated from THP-1 cells [ 127 ]. In addition, in a recent study performed on in vitro THP-1 cell cultures, IS was reported to promote CD163 expression and transition to macrophages with the hallmarks of classical M1 (IL-6, CCL2, COX2) and alternative M2 (IL-10, PPARγ, TGF-β, TIMP-1) phenotypes via AhR/Nrf2 activation.…”
Section: Impact Of Uremic Toxins On Brain Microcirculationmentioning
confidence: 80%
“…Functional GSEA of monocytes from patients with ESRD identified the alteration of major metabolic pathways including glycolysis, oxidative phosphorylation, and fatty acid metabolism, as well as immune response-related pathways such as interferon-α and γ responses, the inflammatory response, and TNF-α signaling via NF-κB ( Figure 3 and Table S3 ). We and others have demonstrated that IS elicits immune responses by its binding to AhR in monocytes/macrophages [ 36 , 37 ]. Thus, identification of immune response-related pathways in GSEA was expected.…”
Section: Discussionmentioning
confidence: 99%